Meningkatkan Responsivitas Pada Sistem Operasi Android Melalui Implementasi Algoritma Penjadwalan Mutakhir - Rakhmadi Rahman; Shalza Naya Dwi Fortuna; Redo Triansyah; Muhammad Akbar Fahrezi (Router : Jurnal Teknik Informatika dan Terapan, 2024)
This research aims to analyze the performance of various CPU scheduling algorithms in increasing the responsiveness of the Android operating system. Using algorithms such as First Come First Served (FCFS), Shortest Job First (SJF), Shortest Remaining Time First (SRTF), and Round Robin, this study evaluates the advantages and disadvantages of each in terms of average waiting time, throughput, and power consumption. Research methods include literature study, algorithm selection and implementation, as well as data testing and analysis. The research results show that choosing the right scheduling algorithm can increase system efficiency and responsiveness, as well as provide recommendations for Android operating system developers and the application developer community. It is hoped that these findings will help in determining the optimal solution for improving the performance of the Android operating system.